AN ANALITIC STUDY: AFFECTIVITY OF GROUP INVESTIGATION MODEL ON STUDENT UNDERSTANDING TECHNIQUE WRITING A PAPER IN STUDY PROGRAM ISLAMIC EDUCATION RELIGION - Suhartono Suhartono; Anik Indramawan (JP : JURNAL PENDIDIKAN, 2020)
Abstract: The purpose of this study is to analysis the affectivity of group investigation model on student understanding writing technique in the first semester. This research is used quasy experiment and the posttest only control group design. The study is done on Indonesia language subject in first- semester students with study program Islamic education religion, class A as experiment class and class B as a control. The data analysis test is used T-test independent with SPSS. The result of the research is showed the average value of test on student understanding writing paper in the first semester with Group Investigation model is 81.17 better than average value of Brainstorming model 71.00 and significant value Independent Samples Test is 0.003 or less from 0.05 (0.003<0.05),  there are many different of influence both of learning model, group investigation model more effective on student understanding writing paper technique in the first semester.Keyword: Group Investigation Model, student understanding